Randomized single-blinded non-inferiority trial of 7 mg/kg pentamidine isethionate versus 4 mg/kg pentamidine isethionate for cutaneous leishmaniaisis in Suriname. - Ricardo V P F Hu; Masja Straetemans; Alida D Kent; Leslie O A Sabajo; Henry J C de Vries; Rudy F M Lai A Fat (Public Library of Science (PLoS), 2015)
Standard treatment of cutaneous leishmaniasis (CL) in Suriname entails three injections of pentamidine isethionate (PI) 4 mg/kg per injection in 7 days (7 day regimen). Compliance to treatment is low and may contribute to increasing therapy failure. A 3 day regimen, including 2 injections of 7 mg/kg in 3 days may increase compliance.In a randomized, single-blinded non-inferiority trial conducted in Suriname, 84 CL patients received the 7 day regimen and 79 CL patients received the 3 day regimen. Primary objective was the proportion of patients clinically cured at 6 weeks follow-up. Secondary objectives were clinical cure at 12 weeks follow-up; parasitological cure at 6 and 12 weeks; adverse and drug related toxicity events recorded one week after the end of treatment and health related quality of life. The non-inferiority margin was set at 15%, 1 sided test, α = 0.1.At 6 weeks follow-up 31 (39%) patients in the 3 day regimen and 41 (49%) patients in the 7 day regimen were clinically cured. Intention to treat (ITT) analyses showed that the difference in proportion clinically cured was -9.6% (90% Confidence Interval (CI): -22.3% to 3.2%). Per protocol (PP) analysis showed that the difference in proportion clinically cured was 0.2% (90% CI: -14.6% to 15.2%). ITT analysis showed that the difference in proportion parasitological cured at 6 weeks was -15.2% (90% CI:-28.0% to -2.5%). PP analyses showed similar results. Non-inferiority could not be concluded for all adverse and toxicological events.We cannot conclude that the 3 day regimen is non-inferior to the 7 day regimen regarding proportion clinically and parasitological cured. Therefore there is no evidence to change the current standard practice of the 7 day regimen for the treatment of CL in Suriname.